Effectiveness of Laser Therapy in Stress Urinary Incontinence Patients: A Systematic Review and Meta-Analysis - Tyas Priyatini; I Putu Gede Kayika; Ruthsuyata Siagian (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: This systematic review and meta-analysis aimed to evaluate the effectiveness of laser therapy in improving urinary and sexual function in women with SUI.Methods: The literature was selected using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) protocol. We did literature searches in several databases, including Science Direct, Pubmed, Google Scholar, Cochrane, ProQuest, and Scopus, from inception until January 2025. Quality assessment was performed using the Cochrane Risk of Bias Tool. Mean differences (MD) with 95% confidence intervals (CI) were calculated using a random-effects model.Result: There were ten journals with 598 participants that met the criteria. The results of the pooled analysis showed a statistically significant improvement in post-laser therapy pad weight (MD = -0.49; 95% CI: -0.97 to -0.01; p = 0.0435). Despite the non-significant differences and heterogeneity found in the meta-analysis of sexual function outcome (MD = -0.49; 95% CI: -0.97 to -0.01; p = 0.0435), the individual studies stated that the sexual function was improved in women with SUI post-laser therapy.Discussion: Laser therapy, particularly CO₂ and Er:YAG modalities, appears effective in enhancing sexual function in women with SUI. Variability in protocols and outcome measures among studies may contribute towards heterogeneity. Most trials had small sample sizes and short follow-ups.Conclusion: Laser therapy shows promise for improving urinary and sexual function in women with SUI, warranting further robust research.Efektivitas Terapi Laser pada Pasien Inkontinensia Urin Stres: Tinjauan Sistematis dan Meta-AnalisisAbstrakTujuan: Tinjauan sistematis dan meta-analisis ini bertujuan untuk mengevaluasi efektivitas terapi laser dalam meningkatkan fungsi urinasi dan seksual pada wanita dengan SUI.Metode: Literatur diseleksi dengan protokol Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA). Penelusuran literatur dilakukan pada beberapa basis data, termasuk Science Direct, Pubmed, Google Scholar, Cochrane, ProQuest, dan Scopus, sejak awal hingga Januari 2025. Penilaian kualitas dilakukan menggunakan Cochrane Risk of Bias Tool. Perbedaan mean (MD) dengan interval kepercayaan (CI) 95% dihitung menggunakan model efek acak.Hasil: Terdapat sepuluh jurnal dengan 598 partisipan yang memenuhi kriteria. Hasil penelitian dari analisis gabungan menunjukan bahwa terdapat peningkatan yang signifikan secara statistik pada pad weight pasca terapi laser (MD = -0,49; 95% CI: -0,97 hingga -0,01; p = 0,0435). Meskipun perbedaan dan heterogenitas yang tidak signifikan ditemukan dalam meta-analisis hasil fungsi seksual (MD = -0.49; 95% CI: -0.97 to -0.01; p = 0.0435), studi individual menyatakan bahwa fungsi seksual membaik pada wanita dengan SUI pasca-terapi laser.Diskusi: Terapi laser, khususnya modalitas CO₂ dan Er:YAG, tampak efektif dalam meningkatkan fungsi seksual pada wanita dengan SUI. Variabilitas dalam protokol dan ukuran hasil di antara studi dapat berpengaruh pada heterogenitas. Sebagian besar uji coba memiliki ukuran sampel kecil dan follow-up yang singkat.Kesimpulan: Terapi laser menunjukkan harapan untuk meningkatkan fungsi urin dan seksual pada wanita dengan SUI, yang menjamin penelitian lebih lanjut yang kuat.